CERTAIN LEGAL ISSUES OF DEVELOPMENT OF RENEWABLE ENERGY IN THE REPUBLIC OF KAZAKHSTAN (Journal of actual problems of jurisprudence, 2024)
The relevance of the research is determined by the low level of development of renewable energy in the Republic of Kazakhstan and the need for effective legal regulation of relations in this area. This is especially acute against the backdrop of the active use of renewable energy sources in the world. In this regard, this article is devoted to identifying legal regulators that could contribute to the active development of renewable energy in the Republic of Kazakhstan. The leading approach to the study of the posed problem is the analysis of regulations in the field of renewable energy in the Republic of Kazakhstan and in the world in order to identify shortcomings and acquire best practices in the legal regulation of the use of renewable energy sources, which made it possible to substantiate a number of proposals for improving the current legislation. Despite the introduction of current preventive mechanisms and innovations to stimulate a reduction in the level of emissions of pollutants into the environment, the need to increase the share of renewable sources in the economic system of the state is present. The practical value of the results obtained lies in providing recommendations in the form of effective mechanisms and consistent measures for their further implementation into the current legislation of Kazakhstan in order to develop the economy and eliminate environmental problems. Keywords: energy, energy resources, alternative energy, renewable energy, renewable energy sources, legal regulation